The Urgency of Guidelines for the Long-term Sustainability of Outer Space Activities for Indonesia - Permatasari, Yunita (Global Strategis, 2019)
The rapid increase in the use and exploration of outer space raises concerns about its sustainability in a sustainable manner. Countries seek multilateral solutions through the guidelines for the long-term sustainability of outer space activities (LTSOSA) which was adopted in June 2019 in the United Nations Committee on the Peaceful Uses of Outer Space (UNCOPUOS) forum. Indonesia as a country that organizes the use and exploration of outer space has an interest in ensuring the security of the implementation of outer space in a sustainable manner. Thus, it is necessary for the mapping of Indonesia's interest in implementing the LTSOSA guidelines. The interest mapping will illustrate the urgency of the LTSOSA guidelines for Indonesia's national security particularly outer space security. The analysis shows that the LTSOSA guidelines contain items related to outer space security which are of vital national importance to Indonesia. This article is expected to become input for Indonesia's attitude and position towards the implementation of the LTSOSA guidelines. Keywords: Indonesia, long term sustainability of outer space activities, outer space security Penggunaan dan eksplorasi antariksa yang semakin pesat menimbulkan kekhawatiran terhadap kelestariannya secara berkelanjutan. Negara-negara mencari solusi secara multilateral melalui pedoman kegiatan antariksa berkelanjutan jangka panjang atau dikenal guidelines for the long-term sustainability of outer outer space activities (LTSOSA) yang disahkan pada Juni 2019 dalam forum United Nations Committee on the Peaceful Uses of Outer Outer space (UNCOPUOS). Indonesia sebagai negara yang menyelenggarakan penggunaan dan eksplorasi antariksa berkepentingan untuk menjamin keamanan penyelenggaraan keantariksaannya secara berkelanjutan. Dengan demikian, perlu adanya pemetaan kepentingan Indonesia dalam mengimplementasikan guidelines LTSOSA. Pemetaan kepentingan akan menggambarkan mengenai urgensi guidelines LTSOSA bagi keamanan nasional Indonesia khususnya bidang keantariksaan. Tulisan ini menemukan bahwa guidelines LTSOSA memuat butir-butir terkait keamanan keantariksaan yang menjadi kepentingan nasional vital bagi Indonesia. Artikel ini diharapkan menjadi bahan masukan sikap dan posisi Indonesia terhadap implementasi guidelines LTSOSA. Kata-kata kunci: Indonesia, keamanan keantariksaan, keberlanjutan kegiatan luar angkasa dalam jangka panjang